THE ISSUES OF MODERNISM AND THE DEVELOPMENT OF ISLAMIC INTELLECTUALISM - Rasid Rasid; Maulana Dwi Kurniasih (Mimbar Agama Budaya, 2022)
Abstract. This article is discusses about the modernist issues in the development of Islamic intellectualism, such as pluralism, liberalism, and secularism. To respond to these difficulties, Muslims must take the following steps: 1) paradigm of thinking, 2) open-mindedness and liberation from religious authoritarianism to open the door of ijtihad so that it is not treacherous in religion, 3) foundation in thinking (world view), namely the principles of life, 4) becoming accustomed to always giving rational arguments and providing information in terms of truth, 5) understanding the function of reason and revelation and not being clashed. Intellectualism in Islam may be fostered through increasing the roles of reason and revelation, which should not conflict with one another. Revelation will be an extreme doctrine in the absence of reason, and reason will be tasteless and undirected in the absence of revelation.Abstrak. Artikel ini membahas tentang isu-isu modernis dalam perkembangan intelektualisme Islam, seperti pluralisme, liberalisme, dan sekularisme. Untuk menjawab kesulitan-kesulitan tersebut, umat Islam harus mengambil langkah-langkah berikut: 1) paradigma berpikir, 2) keterbukaan pikiran dan pembebasan dari otoritarianisme agama untuk membuka pintu ijtihad agar tidak berkhianat dalam agama, 3) landasan berpikir ( pandangan dunia), yaitu prinsip-prinsip kehidupan, 4) membiasakan diri untuk selalu memberikan argumentasi yang rasional dan memberikan informasi yang benar, 5) memahami fungsi akal dan wahyu serta tidak berbenturan. Intelektualisme dalam Islam dapat dibina melalui peningkatan peran akal dan wahyu, yang tidak boleh saling bertentangan. Wahyu akan menjadi doktrin yang ekstrim tanpa adanya akal, dan akal akan menjadi hambar dan tidak terarah tanpa adanya wahyu.